Incremental Health Care Expenditures of the Spouses of Older Adults With Alzheimer's Diseases and Related Dementias (ADRD) - Chu, Jun (Am J Geriatr Psychiatry, 2020)
OBJECTIVE: Previous research has found that having a spouse with Alzheimer's disease and related dementias (ADRD) is associated with higher health care expenditures, however it is unclear if this difference remains after accounting for the demographics and health status of the non-ADRD spouse. This paper aims to estimate the adjusted incremental health care expenditures of having a spouse with ADRD. DESIGN: Cross-sectional study of publicly available survey data (2003–2017 Medical Expenditure Panel Survey). SETTING: Representative sample of U.S. households. PARTICIPANTS: Community-dwelling and married older adults (n = 28,356). MEASUREMENT: Two-part models and recycled prediction techniques to estimate the incremental effects of having a spouse with ADRD on annual health care expenditures, while adjusting for demographics, socioeconomic characteristics, and health conditions. RESULTS: Spouses of older adults with ADRD were older, had worse perceived mental health, and had greater difficulties with activities of daily living, compared to older adults with cognitively normal spouses. Spouses of ADRD patients had significantly higher unadjusted total health care expenditures, however their adjusted incremental expenditure was not significantly greater. After controlling for demographics and health status, ADRD spouses had significantly higher home health care expenditures, but significantly lower outpatient expenditures. CONCLUSION: Results suggested that the higher health care expenditures in older adults with ADRD spouses can be attributed to the higher rate of comorbidities, rate of functional limitations, and mean age in this group. The increased use of home health and decreased use of outpatient in this population suggests the importance of tailoring preventative health care and social services to meet the needs of this group.